2017
DOI: 10.1016/j.actaastro.2016.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a shock wave with an array of particles and effect of particles on the shock wave weakening

Abstract: Two-phase systems that involve gas-particle or gas-droplet flows are widely used in aerospace and power engineering. The problems of weakening and suppression of detonation during saturation of a gas or liquid flow with the array of solid particles are considered. The tasks, associated with the formation of particles arrays, dust lifting behind a travelling shock wave, ignition of particles in high-speed and high-temperature gas flows are adjoined to safety of space flight. The mathematical models of shock wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This will necessitate further research using this method. 25,28 Arunkarthikeyan and Balamurugan demonstrated that freezing the material improves its hardness of the material and increases its wear resistance. Additionally, the microhardness of the WC-Co alloy also increases by approximately 5.7%.…”
Section: Discussionmentioning
confidence: 99%
“…This will necessitate further research using this method. 25,28 Arunkarthikeyan and Balamurugan demonstrated that freezing the material improves its hardness of the material and increases its wear resistance. Additionally, the microhardness of the WC-Co alloy also increases by approximately 5.7%.…”
Section: Discussionmentioning
confidence: 99%